The spatial and temporal development of British prisons from 1901 to the present: The role of de-industrialisation - Jones, Phil Mike (European journal of criminology, 2024)
This paper combines archival data and statistical analysis to investigate the context-specific ways that prisons expanded and affected communities in the UK, focusing closely on the role of the UK's political economy. We present evidence of a significant increase of prisons in the counties where the coal-mining industry was dismantled during the 1980s and 1990s. We identify former coal-mining areas based on Coal Mining Reporting Areas and the methodology used by Beatty and Fothergill (1996) and test if more prisons were opened in former coal-mining areas than non-coal-mining areas per capita post-closures. Using Poisson regression analyses and controlling for population changes, we found that coal-mining counties were significantly more likely to acquire a new prison between 1981 and 2001 than those areas which were not affected by de-industrialisation. We apply Derrida's thinking on hauntology to reexamine the spatial legacy of Thatcherism in these communities as a means to understand history and culture, and the unraveling of the past, present, and future.